The Trajectory of Social Inclusion and Activation of Older People Today - Kh.M. Saralieva, Zaretkhan; A. Sudin, Sergei; V. Ermilova, Anna (International Journal of Psychosocial Rehabilitation, 2020)
The paper reveals region-specific trajectories of social inclusion and activation of older people. It shows the role of ideological perception of social reality that largely determines the choice of social inclusion trajectory. The paper documents findings from authors’ studies carried out in 2014–2018 in three Russian regions. In Nizhni Novgorod Region, three studies were carried out: “Activation of older people in modern society” (N = 160 people), “Activation of older people in physical training and sports” (N = 100 people), and “The potential of older people as perceived by the younger generation: the sociological aspect” (N = 307 people). In the Ivanovo region, the socio-economic situation and social well-being of elderly people were monitored (N = 1160 people); raw data was used obtained from a sociological study of employment of Moscow retirees (N = 150 people). This research work, firstly, identified the dominant social inclusion trajectories of older people, which are “help yourself” and “help others," and secondly, actualized the contextual and above-normative activation trajectory of older people.